Making Mathematics Learning More Engaging for Students in Health Schools through the Use of Apps - Helen Willacy; Nigel Calder (MDPI AG, 2017)
This paper reports on an aspect of a case study of four 11-to-13-year-old students of a Regional Health School (RHS) in New Zealand, using apps on their own mobile devices as part of their mathematics programs. It considers the issue of engaging students in mathematical learning when they are recovering from significant health issues. The paper examines the influence of apps on these students' engagement with mathematical learning through the facilitation of differentiated learning programs. The research design was a case study with semi-structured interviews, questionnaires and observation used to generate the data. A number of themes arose from the data including both the positive and negative influences of apps on student engagement and the influence of apps on facilitating differentiated learning programs. The results indicated that using apps for mathematics had a positive influence on student engagement for most students. The positive student engagement seemed to be partly due to the apps' ability to support differentiated learning.